Impact of Using a Telescoping‐Support Catheter System for Left Ventricular Lead Placement on Implant Success and Procedure Time of Cardiac Resynchronization Therapy. Issue 5 (25th February 2013) - JACKSON, KEVIN P.; HEGLAND, DONALD D.; FRAZIER‐MILLS, CAMILLE; PICCINI, JONATHAN P.; KOONTZ, JASON I.; ATWATER, BRETT D.; DAUBERT, JAMES P.; WORLEY, SETH J.
<x xml:space="preserve">Abstract</x> Background Proper positioning of the left ventricular (LV) lead improves clinical outcomes and survival in patients receiving cardiac resynchronization therapy (CRT). Techniques of LV lead insertion using contrast injection and a telescoping system of delivery catheters to support advancement of the lead into the target branch may allow more efficient, targeted lead placement. We sought to evaluate the impact of an LV lead implant approach using telescoping‐support catheters (group TS) on success rate, lead location, and procedural time compared to standard over‐the‐wire implant techniques (group OTW). Methods Four hundred thirty‐seven consecutive patients undergoing CRT implantation were divided into group TS (n = 105) or group OTW (n = 332) based upon a review of the operative technique used for LV lead implantation. The primary outcome was success of LV lead implantation at the index procedure. Secondary endpoints included optimal positioning of the LV lead and reduction in procedural fluoroscopy time. Results Failed LV lead placement was lower (1.9% vs 8.1%, P = 0.02) and optimal lead positioning was achieved more often for group TS than group OTW (87% vs 75%, P = 0.01). In addition, there were significantly shorter fluoroscopy times for group TS versus group OTW (29.6 minutes vs 41.9 minutes, P < 0.01). Conclusion A CRT‐implant approach using contrast injection and a telescoping‐support catheter system results in fewer failed LV lead implants, improved LV lead location, and shorter procedure times.